The Impact of GERAK PRO on Employee Performance Through Exercise Motivation - Rofii Rofii; Yuni Kusuma Arumsari; M. Jamal Abdul Nasir (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of using the GERAK PRO application on employee performance, with exercise enthusiasm as a mediating variable at PT PLN (Persero) UP3 Mojokerto, Indonesia. The study involved 144 active employees who had used the application for at least three months. A quantitative explanatory approach was applied using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected using a Likert-scale questionnaire to examine the direct and indirect relationships among the variables. The results show that the GERAK PRO application does not directly affect employee performance but significantly increases exercise enthusiasm, which positively improves performance. Exercise enthusiasm fully mediates the relationship between application usage and employee performance. These findings indicate that digital health applications improve performance mainly through behavioral changes, better fitness, and stronger intrinsic motivation. This study contributes to the human resource management literature by confirming the mediating role of exercise enthusiasm in connecting digital wellness applications with employee performance. However, the study is limited to one organizational unit and cross-sectional data, which may reduce the generalizability of its findings.